Serum Transforming Growth Factor Beta2 and Feeding Intolerance in Premature Formula -Fed versus Breast Milk-fed Neonates - Ismail, R I H; Othman, W O A; Abouwarda, M A (QJM : An International Journal of Medicine, 2020)
Abstract Serum Transforming Growth Factor Beta2 and Feeding Intolerance in Premature Formula -Fed versus Breast Milk-fed Neonates Objectives to assess occurance of feeding intolerance and NEC in relation to serum level of TGF-β2 in breast milk versus preterm formula fed neonates. Subjects and Methods a prospective observational study on 80 preterm neonates(≤36weeks gestational age). They were divided to two groups; breast milk fed group(n = 40) and preterm formula fed group(n = 40). They were assessed clinically for feeding intolerance and NEC and laboratory by measurement of TGF-β2 using ELISA technique. Results TGF-β2 serum level was significantly lower in preterm formula fed group than breast fed group;median(interquartile) 500(250-3000) pg/ml vs 7750(6500-11250) pg/ml (p < 0.0001). Both primary outcome(feeding intolerance and NEC) and secondary outcome(respiratory support and sepsis) were negatively correlated to TGF-β2 serum level. TGF-β2 serum level below 1250 pg/ml was found to be a good diagnostic test for feeding intolerance with sensitivity of 75.86% and specificity of 96.08%. Conclusion low serumTGF-β2 level is a specific marker for feeding intolerance in preterm neonate. Using premature formula in premature neonates is not recommended as it is associated with lower serum TGF-β2 and higher incidence of feeding intolerance compared to breast feeding.